Perlindungan Hukum terhadap Korban Pornografi Balas Dendam (Revenge Porn) - I Ketut Bagus Danan Pradana; I Ketut Kasta Arya Wijaya; I B. Gd. Agustya Mahaputra (Verdict: Journal of Law Science, 2026)
Revenge porn is a complex legal and social issue that requires comprehensive handling. Legal protection for victims depends not only on the existence of laws and regulations, but also on the effectiveness of legal implementation, the capacity of law enforcement officials, and social support for victims. The research aims are to investigate the legal regulations of revenge porn in Indonesia and the forms of legal protection for victims of revenge porn. This research is a normative legal study with a conceptual approach, utilizing primary, secondary, and tertiary legal materials collected through document studies and systematically analyzed using deductive and inductive methods. The results show that legal regulations related to revenge porn are still indirect and scattered across various regulations, creating legal uncertainty. Although victim protection has been regulated normatively, its implementation still faces obstacles such as social stigma, difficulties in digital evidence, and limited control of content in cyberspace. Therefore, more specific regulatory updates, increased capacity of law enforcement officials, and strengthening public digital literacy are needed. Synergy between the government, law enforcement officials, victim protection agencies, and the community are the key to create an effective, integrated, and victim-oriented legal protection system.